Europe: core, peripheries and postcolonial relations - Giordano, C. (Социология: теория, методы, маркетинг, 2017)
Most concepts of Europe as a unitary community are characterised by a bipolar scheme where the notion of Europe appears together with contrastive representations of an “anti-Europe” (Arab-Muslim culture, Asia, the Orient, Africa, etc.). There is a mirrored reflective relationship by which the former’s basic traits are identified through a presumed diametrical opposition with the latter’s. However, it is misleading to think of Europe as a united civilisation, or even worse, as a sum of cultural areas. As suggested by a Hungarian historianJeno Szucs, a French historian Fernand Braudel and an American sociologist Immanuel Wallerstein, Europe must be considered as a system of strictly (inter)dependent yet structurally diverse “historical regions”. The rise of the capitalist “world-system” and the emergence of a new international division of labour transformed those regions into core, peripheries and marginal external areas.